2022
DOI: 10.32604/iasc.2022.026020
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Invasive Weed Improved Grasshopper Optimization Algorithm for Cloud Load Balancing

Abstract: In cloud computing, the processes of load balancing and task scheduling are major concerns as they are the primary mechanisms responsible for executing tasks by allocating and utilizing the resources of Virtual Machines (VMs) in a more optimal way. This problem of balancing loads and scheduling tasks in the cloud computing scenario can be categorized as an NP-hard problem. This problem of load balancing needs to be efficiently allocated tasks to VMs and sustain the trade-off among the complete set of VMs. It a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…They used every job in work queue to accomplish balanced scheduling between virtual machines, resource assignment conceded out while taking decrease in makespan into account. Naveen Durai et al [11] suggested HIWIGOA-LB technique exploits IWOA and GOA algorithms to ensure that expected grade of examination and utilization further well-adjusted method, hence achieving potential task scheduling besides load balancing. It combines GOA as well as IWOA utilizing stochastic process and clustering approach to enhance capacity to explore during optimizing and to increase exploitation causes majority of escalation techniques to become trapped in local solutions, outcomes demonstrated that suggested HIWIGO-LB architecture featuring varying sets of fog nodes enlarged resource utilization efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…They used every job in work queue to accomplish balanced scheduling between virtual machines, resource assignment conceded out while taking decrease in makespan into account. Naveen Durai et al [11] suggested HIWIGOA-LB technique exploits IWOA and GOA algorithms to ensure that expected grade of examination and utilization further well-adjusted method, hence achieving potential task scheduling besides load balancing. It combines GOA as well as IWOA utilizing stochastic process and clustering approach to enhance capacity to explore during optimizing and to increase exploitation causes majority of escalation techniques to become trapped in local solutions, outcomes demonstrated that suggested HIWIGO-LB architecture featuring varying sets of fog nodes enlarged resource utilization efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…This form of unemployment is an inherent component of the technologically-driven phenomenon known as creative destruction, as described by [35] and incorporated into Kondratieff's theory of long waves in economic expansion. It is not unfounded to postulate, then, that the introduction of technical advancements may, in the beginning stages, potentially have a negative implication on individuals' overall satisfaction of life by leading to a significant increase in unemployment rates.…”
Section: Lifestyle Fears and Human Valuesmentioning
confidence: 99%
“…Additionally, robot factors (RF), like automation and reliability, as well as human factors (HF), including experience, and qualities, also play a significant role in shaping HRC. According to [38], conventional manufacturing robots exert an impact on human-robot collaboration (HRC) without including feedback mechanisms. This implies that in traditional robotics, the responsibility for adapting to various elements of HRC falls on the operator rather than the robot itself.…”
Section: Fig 3 Collaboration-centered Concept Mapmentioning
confidence: 99%